The Nature and Role of Regional Agreements in International Environmental Politics: Mapping Agreements, Outlining Future Research - Jörg Balsiger; Miriam Prys; Niko Steinhoff (German Institute of Global and Area Studies (GIGA), 2012)
Global agreements to mitigate climate change, conserve biodiversity or combat desertification typically take center stage in scholarly discussions about international environmental politics. Even though the United Nations Environment Programme reported ten years ago that regional agreements make up two-thirds of all international treaties, regional cooperation has by comparison either received scant attention or been conceptually and empirically lumped together with global treaties. This lack of knowledge about the historical and current scope of regional governance is a serious obstacle to understanding the architecture of global environmental governance and to overcoming current bottlenecks in international environmental cooperation. In response, we report on the outcome of an analysis that complements the most comprehensive database on international environmental agreements (iea.uoregon.edu) with variables for analysis at the regional level. We introduce a multidimensional typology of regional agreements based on contiguous/noncontiguous agreement membership, contiguous/noncontiguous spatial ambit, and whether membership and ambit are adjoining and/or coextensive. We discuss the theoretical and empirical relevance of the different types of agreements and the nature and prevalence of special cases. Given the previous lack of research in this area, our primary purpose is to present a systematic account of regional environmental governance, leaving causal analysis to our own and others' future research. We identify a number of knowledge gaps and analytical directions in the conclusion.
Keywords: 300; regional cooperation; environmental politics; typology of international cooperation; Klimaveränderung; Umweltabkommen; Klassifikation; Welt